1987
DOI: 10.1172/jci113079
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cation transport by low doses of glucocorticoids in in vivo adrenalectomized rat colon.

Abstract: A dose response curve for glucocorticoid-induced proximal and distal colonic cation transport in vivo was established in adrenalectomized rats. All doses (0.5-50 nmol/100 g body wt) stimulated sodium absorption. Distal sodium absorption did not saturate at dexamethasone levels that saturate the glucocorticoid receptor but also bind to > 35% of aldosterone receptors. Saturation of the pure glucocorticoid response occurred in both segments with RU26988, a synthetic glucocorticoid that does not occupy aldosterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…20 Corticosteroids could affect Bruch membrane via their known inhibition of collagen synthesis. 152 Finally, epithelial water and ion transport are altered by corticosteroids, 16,72,182,197 and this might impair the barrier function of the RPE. Arndt and colleagues studied RPE tissue in vitro and showed that administration of hydrocortisone decreased the transepithelial membrane potential and resistence.…”
Section: Pathophysiologymentioning
confidence: 99%
“…20 Corticosteroids could affect Bruch membrane via their known inhibition of collagen synthesis. 152 Finally, epithelial water and ion transport are altered by corticosteroids, 16,72,182,197 and this might impair the barrier function of the RPE. Arndt and colleagues studied RPE tissue in vitro and showed that administration of hydrocortisone decreased the transepithelial membrane potential and resistence.…”
Section: Pathophysiologymentioning
confidence: 99%
“…There is abundant experimental evidence that adrenal corticosteroids increase and adrenalectomy decreases Na + transport and the permeability of the apical membrane of colonocytes to Na § [2,3,6,29,41]. The corticosteroids increase Na § flux into the cell which in turn stimulates the active Na + extrusion via the Na,K pump, because the intracellular Na + activity remains approximately constant in spite of the manifold variations of Na + current across the epithelium [38].…”
Section: Introductionmentioning
confidence: 99%
“…The curves were calculated using an equa-tion derived from Michaelis-Menten kinetics with three noninteracting Na + binding sites which gave better fit than the model of highly cooperative sites [17]. The noninteracting model equation was (2) where Isc was the value of the short-circuit current at various concentrations of Na +, 1 max the maximal SC value oflsc, KNa the substrate concentration at which 50% of binding sites were occupied and [Na § the mucosal Na + concentration. The K0.…”
mentioning
confidence: 99%
“…DOCA treatment restored K-NPPase in adrenalectomized rats. The treatment with dexamethasone had a much smaller effect than with DOCA even though a dose of dexamethasone of 5 ~g per 100 g body wt per 12 h occupied more than 90% of distal colon glucocorticoid receptors and less than 30% of mineralocorticoid receptors, and a dose 0.5 lJg per 100 g body wt per 12 h occupied more than 60% of glucocorticoid and less than 10% of mineralocorticoid receptors (Bastl, 1987(Bastl, , 1988. Thus, mineralocorticoids seem to exert a decisive role in the regulation of colonic Na,K-ATPase, even if the possibility that glucocorticoids act through high-specificity glucocorticoid receptors cannot be excluded.…”
Section: Discussionmentioning
confidence: 90%